Sifat Mekanik Berkas Vaskular Batang Kelapa Sawit - Saroji, Asmaliah; Lim, K. O. (Universiti Putra Malaysia Press, 2000)
The objective of the project is to investigate the relationship between the stress-strain characteristics of oil palm trunk vascular bundles and its moisture content. Based on the stress-strain graphs, the mechanical characteristics are then related to the microstructure of the vascular bundles. The results show that for all samples tested, 3 zones of deformation are found i.e an initial zone that is slightly curving, a plateau zone and finally a linear zone. The existence of the plateau zone is then explained in terms of the vascular bundle microstructure. AJ; a result of the presence of the plateau zone, the stress-strain curve is then described by 2 modulus of elasticity i.e the initial modulus and final modulus. The final modulus was found to be higher than the initial modulus thus indicating that the vascular bundles become stiffer after encountering the plateau zone. The maximum stress and final modulus of the vascular bundles were found to increase when the moisture content of the vascular bundles decreased.